Constitutive Model of Swelling Gypsum Rock - Chongbang Xu; Xiaojing Gao; Kaishun Zhang; Zhiguo Liu; Fan Zhao (Advances in Civil Engineering)
Swelling of soft rock, such as gypsum rock, is one of the major threats in tunnel engineering, causing structure damages such as floor heave and inward movement of sidewalls during construction and operation. It is of practical significance to study the swelling mechanical behavior of such rocks by tests. Swelling strain tests and swelling stress tests were performed by swelling test apparatus to study the variation of swelling strain with time and the swelling stress-strain relationship for gypsum rock samples, respectively. Three stages of the swelling strain on the time-strain curve of gypsum rock samples were noticed, which are defined as rapid swelling stage, slow swelling stage, and steady stage. And it was further found that the swelling strain caused in the slow swelling stage is of 76% of the total swelling strain. A constitutive model is proposed to describe the stress-strain relationship in swelling considering the swelling deformation and swelling pressure. The proposed model was verified using test data, which shows good agreements in describing the relationship between swelling strain and swelling stress, also in the conditions of maximum swelling strain and maximum swelling stress under lateral restraint situations.